Application of dielectric spectroscopy and DSC to the study of relaxations in some copolymeric hydrogels - Ahmad, Mansor; O'Mahony, John P.; Huglin, Malcolm B.; Davis, Thomas P. (1995)
The nature of water in copolymeric N‐vinyl pyrrolidone/methyl methacrylate hydrogels has been investigated using dielectric thermal analysis (DETA) and differential scanning calorimetry (DSC). Dielectric tan δ measurements are reported over a frequency range 500 Hz‐20 kHz and a temperature range of −140 to +20°C. The observed complex relaxations were attributed to the mobility of water and the relaxation processes of the copolymer matrix. In addition DSC was used to measure the melting endotherm of water in gels partially swollen to a pseudoequilibrium. The resultant data were fitted to a two‐phase approximation model. © 1995 John Wiley & Sons, Inc. Copyright © 1995 John Wiley & Sons, Inc.